Local empty fruit bunch concrete an investigation on flexural performance - Joehanis Jabiul (2022)
The focus of this project is to study the flexural performance of natural fiber concrete, which in this research is the oil palm empty fruit bunch empty fruit bunch EFB fiber. The oil palm EFB fiber has a great potential to be used as reinforcement filler for concrete due to its mechanical and structural properties. Palm oil EFB fiber structure consists of cellulosic structure that can also be found in other plant fiber. The significance of oil palm EFB fiber to be used as reinforcement filler is that they were readily available as a waste material in Oil Palm agricultural sectors. Since Malaysia is one of the largest oil palm producers, the oil palm EFB fiber decomposition has become one of the major problems faced by this agricultural sector. Other than damping the waste to be decomposed naturally, this waste can be turned into valuable products. By using fabrication methods based on recognized engineering standards such as American Society for Testing and Materials ASTM and British Standard BS, the ability of oil palm EFB fiber as reinforcement fillers in concrete can be achieve. Compared to conventional concrete, flexural performance of oil palm EFB fiber concrete should be better than conventional concrete. However, the result obtained does not meet the expected outcome. This is likely due poor adhesion between the oil palm EFB fiber and concrete matrix material used. Comparison between the obtained result with other research was done, and improvement method was discussed. Improvement proposed is including irradiation of cellulose molecule within the oil palm EFB fiber and using hyper-plasticizer for better dispersion of cement particle and better penetration into oil palm EFB fiber cell wall. Gamma radiation may induce the degradation of cellulose structure, which produce free radicals that can form a stronger interphase bonding with cement particles as hydration process take place.